THE EFFECTS OF INTELLIGENCE QUOTIENT AND CRITICAL THINKING ABILITY TOWARDS STUDENTS’ SPEAKING SKILL - Octavia Puspaning Maharani (Universitas Indraprasta PGRI, 2021)
This research is aimed at knowing the effect of intelligence quotient and critical thinking ability towards students’ speaking skill. The research methodology is quantitative research design with the use of a survey with multi-correlation technique using some samples from a number of population and using a test used for data collection. The number of the samples is two classes from two government colleges in Bogor, West Java. The result of the research shows that; 1). There is a significant effect of intelligence quotient and critical thinking ability towards students’ speaking skill at Government College in Bogor that was proven by the value of Sig. 0.000 < 0.05 and Fobserved = 130.848. Both independent variables had given a contribution of 84.8% to the students’ speaking skill. 2). There is significant effect of intelligence quotient towards students’ speaking skill at Government College in Bogor that was proven by the value of Sig. 0.000 < 0.05 and Tobserved = 4.884. 3). There is a significant effect of the critical thinking ability towards students’ speaking skill at Government College in Bogor that was proven by the value of Sig. 0.000 < 0.05 and Tobserved = 4.382.Key Words: Intelligence Quotient; Critical Thinking; Speaking Skill.